'Peeling back the mask': Remediation and remix of Kenya's news into popular culture. (1st March 2015) - Omanga, Duncan
This article probes how two 'ordinary news' events were remediated and remixed by ordinary users, journalists and professional musicians, and were circulated as popular music in Kenya. Specifically, using TV news clips and music videos uploaded on YouTube, the article reveals how the digital media allow news events to be emptied of their 'hard news' and to be circulated as either entirely new, or as modified artefacts of popular culture. To achieve its aims, the article borrows and modifies Bolter and Grusin's logic of remediation to show the conflations and distinctions between news and its digital derivatives, and also their metamorphosis from hard news to popular music. In particular, the article concludes that the process of the remediation of news into remix is a factor of technology, content and context, whose interplay ambiguously interrogates the notion of erasure/invisibility (immediacy) and construction/visibility (hypermediacy).